2014
DOI: 10.1093/gji/ggt502
|View full text |Cite
|
Sign up to set email alerts
|

Resolution of non-double-couple components in the seismic moment tensor using regional networks—I: a synthetic case study

Abstract: We perform a detailed synthetic study on the resolution of non-double-couple (non-DC) components in the seismic moment tensors from short-period data observed at regional networks designed typically for monitoring aftershock sequences of large earthquakes. In addition, we test two different inversion approaches-a linear full moment tensor inversion and a nonlinear moment tensor inversion constrained to a shear-tensile source model. The inversions are applied to synthetic first-motion P-and S-wave amplitudes, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
29
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 59 publications
(38 citation statements)
references
References 25 publications
7
29
1
Order By: Relevance
“…The errors in the non-DC components are mainly projected into the CLVD component which displays about three times higher scatter than the ISO component. Similar observations are reported by Stierle et al (2014).…”
Section: Discussion a N D C O N C L U S I O N Ssupporting
confidence: 92%
“…The errors in the non-DC components are mainly projected into the CLVD component which displays about three times higher scatter than the ISO component. Similar observations are reported by Stierle et al (2014).…”
Section: Discussion a N D C O N C L U S I O N Ssupporting
confidence: 92%
“…This kinematic model is supported by combined strike-slip and normal-faulting mechanisms for Izmit aftershocks [Bohnhoff et al, 2006] in this area. Such progressing basin development is also in accordance with observed positive isotropic source components of Izmit aftershocks [Stierle et al, 2014a[Stierle et al, , 2014b and rotations of the local stress tensor orientation [Ickrath et al, 2014[Ickrath et al, , 2015 in the early post-Izmit deformation in the area. However, these observations may also reflect generation of rock damage in the earthquake source volumes [e.g., Ben-Zion and Ampuero, 2009;Ross et al, 2015] and a variety of fluid-related effects [e.g., Hardebeck and Hauksson, 2001;Ma et al, 2012] rather than the structural evolution suggested above.…”
Section: Discussionsupporting
confidence: 85%
“…Aftershock recordings provided information for detailed studies of the seismotectonic setting after the Izmit and Düzce mainshocks [ Bohnhoff et al , ; Bulut et al , ; Bohnhoff et al , Crustal response to spatiotemporal variations of coseismic slip along the combined 1999 Izmit‐Düzce rupture, submitted to Tectonophysics , 2015]. The results in part also documented a significant rotation of the local stress tensor [ Ickrath et al , , ] and substantial nondouble components [ Stierle et al , , ] below the Akyazi Basin within weeks following the mainshock. The Karadere Segment is located between the Akyazi and Düzce releasing bends and is a steeply (~67°) north dipping strike‐slip fault [ Bulut et al , ], reflecting mostly right‐lateral strike‐slip aftershocks in general correspondence with the regional stress field [ Bohnhoff et al , ; Görgün et al , ].…”
Section: Study Area and Datamentioning
confidence: 99%
“…The uncertainties of the CLVD component are much higher than that of the ISO, because the CLVD is more sensitive to errors in the inversion than the ISO. This observation is consistent with the results in other areas (Stierle, Bohnhoff, & Vavryčuk, ; Stierle, Vavryčuk, et al, ; Vavryčuk, ). The error limits of the ISO at the 95% confidence level are less than 2% in all three cases and are much lower than the spatial and temporal variations of the ISO as well.…”
Section: Resultssupporting
confidence: 93%